From Diabetic Nephropathy to End-Stage Renal Disease: The Effect of Chemokines on the Immune System - Yuheng Qiu; Jingyi Tang; Qihan Zhao; Yuhua Jiang; Yu Ning Liu; Wei Jing Liu (Journal of Diabetes Research)
Background. Diabetic nephropathy (DN) is a major cause of end-stage renal disease (ESRD), and there is growing evidence to support the role of immunity in the progression of DN to ESRD. Chemokines and chemokine receptors (CCRs) can recruit immune cells to sites of inflammation or injury. Currently, no studies have reported the effect of CCRs on the immune environment during the progression of DN to ESRD. Methods. Differentially expressed genes (DEGs) from the GEO database were identified in DN patients versus ESRD patients. GO and KEGG enrichment analyses were performed using DEGs. A protein-protein interaction (PPI) network was constructed to identify hub CCRs. Differentially expressed immune cells were screened by immune infiltration analysis, and the correlation between immune cells and hub CCRs was also calculated. Result. In this study, a total of 181 DEGs were identified. Enrichment analysis showed that chemokines, cytokines, and inflammation-related pathways were significantly enriched. Combining the PPI network and CCRs, four hub CCRs (CXCL2, CXCL8, CXCL10, and CCL20) were identified. These hub CCRs showed an upregulation trend in DN patients and a downregulation trend in ESRD patients. Immune infiltration analysis identified a variety of immune cells that underwent significant changes during disease progression. Among them, CD56bright natural killer cell, effector memory CD8 T cell, memory B cell, monocyte, regulatory T cell, and T follicular helper cell were significantly associated with all hub CCR correlation. Conclusion. The effect of CCRs on the immune environment may contribute to the progression of DN to ESRD.